Mapping Microproteins and ncRNA-Encoded Polypeptides in Different Mouse Tissues - Pan, Ni; Wang, Zhiwei; Wang, Bing; Wan, Jian; Wan, Cuihong (Frontiers in Cell and Developmental Biology, 2021)
Small open reading frame encoded peptides (SEPs), also called microproteins, play a vital role in biological processes. Plenty of their open reading frames are located within the non-coding RNA (ncRNA) range. Recent research has demonstrated that ncRNA-encoded polypeptides have essential functions and exist ubiquitously in various tissues. To better understand the role of microproteins, especially ncRNA-encoded proteins, expressed in different tissues, we profiled the proteomic characterization of five mouse tissues by mass spectrometry, including bottom-up, top-down, and de novo sequencing strategies. Bottom-up and top-down with database-dependent searches identified 811 microproteins in the OpenProt database. De novo sequencing identified 290 microproteins, including 12 ncRNA-encoded microproteins that were not found in current databases. In this study, we discovered 1,074 microproteins in total, including 270 ncRNA-encoded microproteins. From the annotation of these microproteins, we found that the brain contains the largest number of neuropeptides, while the spleen contains the most immunoassociated microproteins. This suggests that microproteins in different tissues have tissue-specific functions. These unannotated ncRNA-coded microproteins have predicted domains, such as the macrophage migration inhibitory factor (MIF) domain and the Prefoldin domain. These results expand the mouse proteome and provide insight into the molecular biology of mouse tissues.